2019
DOI: 10.1108/jima-02-2018-0025
|View full text |Cite
|
Sign up to set email alerts
|

Attitude: mediator of subjective norm, religiosity and intention to adopt Islamic banking

Abstract: Purpose The purpose of this paper is to report on the results of a study carried out to examine the mediating effect of attitude in the relationship between subjective norm, religiosity and intention to adopt Islamic banking in a developing secular state like Uganda. Design/methodology/approach This study’ research design was cross sectional. Closed ended questionnaires were distributed to 258 managers of micro businesses in Uganda. Data were analyzed with the help of SPSS v22 and MedGraph program (Excel ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
101
1
19

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(135 citation statements)
references
References 25 publications
14
101
1
19
Order By: Relevance
“…The findings on the linkage between attitudes and the adoption of microfinance services is consistent with previous research, such as that undertaken by Jaffar and Musa (2016) who also found a positive relationship between attitude and the intention to use Islamic microfinance. Similar findings are also obtained by Bananuka et al (2019) in the context of Uganda and Zinser (2019) for US Muslim consumers. On the other hand, Maulana et al (2018) found that for Indonesian consumers, among the three main beliefs, only perceived behavioural control was found to have a positive and significant influence in the use of Islamic microfinance.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The findings on the linkage between attitudes and the adoption of microfinance services is consistent with previous research, such as that undertaken by Jaffar and Musa (2016) who also found a positive relationship between attitude and the intention to use Islamic microfinance. Similar findings are also obtained by Bananuka et al (2019) in the context of Uganda and Zinser (2019) for US Muslim consumers. On the other hand, Maulana et al (2018) found that for Indonesian consumers, among the three main beliefs, only perceived behavioural control was found to have a positive and significant influence in the use of Islamic microfinance.…”
Section: Discussionsupporting
confidence: 83%
“…Jaffar and Musa ( 2016) conduct a study among the non-users' business owners to examine their intention to use Islamic financing and found a positive relationship between attitude and adoption intention to use Islamic finance. A recent study of Bananuka et al (2019) shows that the attitude of business managers of small firms in Uganda influences the adoption intention of Islamic banking services. Zinser ( 2019) conducted a study among the United States (US) Muslims to determine their willingness to use Islamic financial services.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Alam et al (2012) found that religiosity is an important element because it is able to influence individual in terms of cognitive and behavior. To the contrary, a research conducted by Bananuka et al (2019) indicates that religiousity has a positive significant relationship with the intention to adopt Islamic banking. A part from ideology, religiuosity is proven to have positive association the adoption of Islamic banking intention (Kaawaase et al, 2019).…”
Section: Religiosity and Intention To Use Islamic Banking Productsmentioning
confidence: 89%
“…However, there were very few studies that introduced attitude as a mediator between religiosity and Muslims' intention to visit homestays. A study among Ugandan found that Islamic banking adoption was positively influenced by customer attitude (Bananuka et al, 2019). Apart from that, consumer's attitude was also found to mediate the relationship of religiosity towards the Ugandan people's intention to adopt Islamic banking in Uganda.…”
Section: The Mediating Role Of Attitudementioning
confidence: 97%
“…Nevertheless, several recent studies, such as Bananuka et al (2019), Bouteraa (2020), Nora & Minarti (2016), and Souiden & Rani (2015) found that religiosity has an indirect influence on purchase intention with attitude as the mediator. However, there were very few studies that introduced attitude as a mediator between religiosity and Muslims' intention to visit homestays.…”
Section: The Mediating Role Of Attitudementioning
confidence: 99%